The around architecture for dynamic location-based services - José, Rui (2003)
This paper presents a generic concept of location-based service as an abstraction for supporting the association between computational resources and location. The objective is to extend the advantages of service-based architectures to the development of location-based systems, thus providing a more open and extensible alternative to the “vertical” approaches typically used in this type of system. The novel AROUND architecture is proposed as an approach for supporting location-based services in the Internet environment. AROUND provides a service location infrastructure that allows applications to select services that are specifically associated with their current location. The architecture includes a flexible scope model that defines the association between services and location, and a service location infrastructure organised by spatial criteria and optimised for location-based queries. Based on a prototype implementation of this architecture, we have developed two case studies that illustrate the use of this approach for developing location-based systems. The overall results provide a valuable insight into the applicability of the architecture, and suggest that this model of location-based services can provide a useful approach for the development of a wide range of location-based applications.